2013
DOI: 10.1016/j.jhevol.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive costs for everyone: How female loads impact human mobility strategies

Abstract: While mobility strategies are considered important in understanding selection pressures on individuals, testing hypotheses of such strategies requires high resolution datasets, particularly at intersections between morphology, ecology and energetics. Here we present data on interactions between morphology and energetics in regards to the cost of walking for reproductive women and place these data into a specific ecological context of time and heat load. Frontal loads (up to 16% of body mass), as during pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(128 citation statements)
references
References 78 publications
8
114
0
6
Order By: Relevance
“…gas exchange variables, HR, SpO 2 , and NIRS signals) were averages of the last 2 min of standing prior to starting walking. A single sample with an average final 1-min pulmonary V̇O 2 value (ml min −1 ) and V̇CO 2 (ml min −1 ) at each gait speed were used to obtain the energy expenditure (EE) during walking, based on the following equation (Brouwer, 1957; Masschelein et al, 2012): To calculate each particular C w , this equation can be transported as follows: The C w - v relationship can be mathematically described by the following equation (Abe et al, 2015; Wall-Scheffler and Myers, 2013): where the constants a, b, and c are determined by the least squares regressions with the actually observed C w values at each gait speed. A differential function of the original quadratic Eqn (2) of each individual can be described as follows: Then, the individual ES was determined at the gait speed when C w ′ ( v ) equaled zero, that is, the individual ES could be observed using the following equation: We recently reported that standing V̇O 2 amounted approximately 50% of the absolute V̇O 2 at the level gradient at 0.667 m s −1 under normoxia, indicating that a careful consideration should be necessary to calculate C w and ES by subtracting the standing metabolic rate (Abe et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…gas exchange variables, HR, SpO 2 , and NIRS signals) were averages of the last 2 min of standing prior to starting walking. A single sample with an average final 1-min pulmonary V̇O 2 value (ml min −1 ) and V̇CO 2 (ml min −1 ) at each gait speed were used to obtain the energy expenditure (EE) during walking, based on the following equation (Brouwer, 1957; Masschelein et al, 2012): To calculate each particular C w , this equation can be transported as follows: The C w - v relationship can be mathematically described by the following equation (Abe et al, 2015; Wall-Scheffler and Myers, 2013): where the constants a, b, and c are determined by the least squares regressions with the actually observed C w values at each gait speed. A differential function of the original quadratic Eqn (2) of each individual can be described as follows: Then, the individual ES was determined at the gait speed when C w ′ ( v ) equaled zero, that is, the individual ES could be observed using the following equation: We recently reported that standing V̇O 2 amounted approximately 50% of the absolute V̇O 2 at the level gradient at 0.667 m s −1 under normoxia, indicating that a careful consideration should be necessary to calculate C w and ES by subtracting the standing metabolic rate (Abe et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Stern [46] raised concerns that we share about the costs of vertical oscillations and stride length, suggesting that specific stride lengths and levels of centre of mass oscillation may provide energetic efficiency. Work by WallScheffler and co-workers [69,70] suggests that a broad pelvis may provide the additional important benefit of increasing speed flexibility relative to locomotor cost, especially in short-legged individuals. Furthermore, Wall-Scheffler and co-workers have found that a wider pelvis reduces the cost of carrying an infant, which would have been an important energy drain for early female bipeds [69,71,72].…”
Section: Pelvic Evolution In Early (Non-homo) Homininsmentioning
confidence: 99%
“…Because females represent the energetic bottleneck for reproduction, and female fertility is sensitive to even minimal energetic perturbations [13,14,71], it is unlikely that females would bear the energetic burden of increasing their walking speed. Pregnant and lactating females are particularly vulnerable to energetic strain and are not likely to increase their speed; pregnant women show steep CoT curves as well as slower optimal and preferred speeds than when they are not pregnant [72,73].…”
Section: Individuals Walking Togethermentioning
confidence: 99%
“…Females would travel this distance in 3.18 hours, presuming they were walking at their unloaded optimal speed. Women walking unloaded may not be likely given that most ethnographic reports of women are that they are generally carrying children, food, and household items [25,30,75] and thus may be walking around their loaded optimum, which is significantly slower [72]. If males chose to slow down and walk at the female unloaded optimum, it would cost them 52 kJ more to travel this distance.…”
Section: Individuals Walking Togethermentioning
confidence: 99%
See 1 more Smart Citation